Revisiting Project-Based Learning and Digital Technology Integration: Paradoxical Effects on Students’ Learning Motivation in Secondary Education - Virgini Koilam; Romi Mongdong; Zoya F. Sumampow (JR Education, 2026)
This study examines the effects of Project-Based Learning (PjBL) management and digital technology utilization on students’ learning motivation in a secondary education context. Despite the widespread adoption of innovative pedagogical approaches and digital tools, student motivation remains a persistent challenge, particularly in developing educational settings. This research aims to investigate both the partial and simultaneous influences of these variables on student motivation. A quantitative correlational design was employed, involving students from a public junior high school in Indonesia. Data were collected using a structured questionnaire based on validated theoretical frameworks, including constructivist learning theory, Self-Determination Theory, and Technological Pedagogical Content Knowledge (TPACK). The data were analyzed using descriptive statistics and multiple linear regression techniques. The findings reveal that both PjBL management and digital technology utilization have statistically significant but negative effects on students’ learning motivation, both individually and simultaneously. These results suggest that the current implementation of these educational innovations may not effectively support student engagement. Factors such as inadequate planning, limited teacher facilitation, unstructured use of technology, and cognitive overload are identified as potential contributors to the decline in motivation. This study highlights the importance of effective educational management in ensuring the success of instructional innovations. It emphasizes that the integration of PjBL and digital technology must be carefully designed, systematically implemented, and continuously evaluated to achieve positive learning outcomes. The findings contribute to the existing literature by providing a critical perspective on the potential drawbacks of educational innovation and offer practical implications for educators, school leaders, and policymakers.